ToF‐SIMS analysis of chemical composition of atmospheric aerosols in Beijing. (6th November 2019) - Jia, Feifei; Wu, Kui; Che, Yanli; Zhang, Yanyan; Zeng, Fangang; Luo, Qun; Yu, Xiao‐Ying; Zhu, Zihua; Zhao, Yao; Wang, Fuyi
Abstract : Atmospheric aerosols collected from each season in urban Beijing have been studied using time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS). The chemical composition of atmospheric aerosol particles during various atmospheric pollution levels was analyzed and distinguished by principal component analysis (PCA). The differences and sources of the components of the aerosol particles were explored. The results showed that the fine particulate matter from heavily polluted days mainly consists of inorganic salts and organic compounds, such as hydrocarbons, nitrogen‐ or sulfur‐containing hydrocarbons, and their oxides. Samples collected from clean days in the four seasons were also analyzed. Only the samples collected in spring showed a significant difference from the other three seasons. We concluded that the main source of pollution in the Beijing urban area was fossil fuel combustion from motor vehicles.